2004
DOI: 10.1002/er.1027
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on steam-added mild combustion

Abstract: SUMMARYNumerical study on flame structure and NO emission is conducted covering a wide range of atmospheric temperature, high temperature, and mild combustion regimes in H 2 -Air laminar flames diluted with steam. Special concern is focused on the difference of flame structure and NO emission behaviour between hightemperature combustion and mild combustion modes. The important role of chemical effects of added steam in flame structure and NO emission behaviour is also discussed. It is seen that there exists an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…Since previous studies have already shown that the high heating rate is one of the main reasons for high volatile release rate, [52][53][54] it is deduced that the heating rate of the outer stream is higher than that of the inner stream. Equations (12) and (14) indicate a positive correlation between the concentration of NO and the reduction rate of NO by reacting with HCN and NH 3 . The IFRF furnace characterizes the strong recirculation of flue gas.…”
Section: No Emission Originated From Fuel Pathmentioning
confidence: 99%
See 2 more Smart Citations
“…Since previous studies have already shown that the high heating rate is one of the main reasons for high volatile release rate, [52][53][54] it is deduced that the heating rate of the outer stream is higher than that of the inner stream. Equations (12) and (14) indicate a positive correlation between the concentration of NO and the reduction rate of NO by reacting with HCN and NH 3 . The IFRF furnace characterizes the strong recirculation of flue gas.…”
Section: No Emission Originated From Fuel Pathmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] The essence of this technology for coal combustion is to achieve strong recirculation of the injected streams so that the coal particles are heated and combusted in a highly substoichiometric condition. [2][3][4][5][6][7][8][9][10][11][12][13] The essence of this technology for coal combustion is to achieve strong recirculation of the injected streams so that the coal particles are heated and combusted in a highly substoichiometric condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the promoting effects of TBHP addition under different initial temperatures, pressures, and equivalence ratios were investigated by CHEMKIN‐PRO software . Furthermore, the acting mechanism of TBHP addition was studied in detail using the mole fraction and rate of production and consumption (ROP) analysis, sensitivity analysis, and reaction pathway analysis …”
Section: Introductionmentioning
confidence: 99%
“…All the nozzles and exhausts were at the bottom of the furnace. This MILD combustion setup has produced data on various experiments, including fuel tests, flame tests, NO x tests, and heat exchanger tests (Christo and Dally, 2005;Colorado et al, 2009;Dally et al, 2002Dally et al, , 2004Dally et al, , 2010de Joannon et al 2009de Joannon et al , 2010Flamme, 2004;Li et al, 2011b;Lou et al, 2007;Maruta et al, 2000;Medwell et al, 2007Medwell et al, , 2008Mi et al, 2009;Mörtberg et al, 2006;Oryani et al, 2011;Park et al, 2004;Stankovic, 2006). MILD combustion technology is still not fully commercialized and well adopted in the furnace industry, thus it is very important to conduct substantial fundamental and applied research (Cavaliere et al, 2008;Danon, 2011;Li et al, 2011b;Parente et al, 2011aParente et al, , 2011b.…”
Section: Recent Trends In Mildmentioning
confidence: 99%